Educación ambiental para el aprovechamiento de desechos sólidos orgánicos e inorgánicos en el mercado municipal Solanda DMQ, 2016 - Mejía Yanez, Carmen Alexandra (2017)
This research to aims determine the influence of environmental education to the use of organic and inorganic solid wastes Municipal Market traders Solanda. In this project, an analysis was made on the use of solid wastes that are generated in the Market which are not used because of the lack of information that the merchants own. The methodology is framed in the descriptive, qualitative and quantitative approach, corresponding to a socio-educational project whose purpose was to know the situation through the intervention of the study group and the researcher, relying on bibliographical, documentary and field research. As proposal, the preparation of an environmental guide on the use of solid waste is structured, which is structured by environmental activities and workshops that seek to create an environmental culture based on ecological values.